2021
DOI: 10.1177/00131245211027369
|View full text |Cite
|
Sign up to set email alerts
|

School Transit and Accessing Public School in Detroit

Abstract: Students in the Detroit Public Community Schools District (DPSCD) have the highest rate of chronic absence (missing 10% or more of school days) among large districts in the United States. Additionally, students in DPSCD are among the poorest students in the country, often lacking access to reliable personal transportation or public transit to facilitate getting to school. Although DPSCD offers school-sponsored transit, only 30% of K-8 students were eligible for such transit in 2018 to 2019. Through the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Initially serving 10 charter and DPSCD schools in Northwest Detroit, the GOAL (Get On And Learn) bus picks students up on designated street corners and drops them off at different schools. While GOAL expanded to more schools in subsequent years, there have been some issues with take-up, coordination, and cost, raising questions about its overall effectiveness as a strategy (Edwards et al 2019;Pogodzinski et al 2021).…”
Section: Discussion and Policy Alternativesmentioning
confidence: 99%
“…Initially serving 10 charter and DPSCD schools in Northwest Detroit, the GOAL (Get On And Learn) bus picks students up on designated street corners and drops them off at different schools. While GOAL expanded to more schools in subsequent years, there have been some issues with take-up, coordination, and cost, raising questions about its overall effectiveness as a strategy (Edwards et al 2019;Pogodzinski et al 2021).…”
Section: Discussion and Policy Alternativesmentioning
confidence: 99%
“…Empirical evidence suggests, with regard to the infrastructure component, that investments that improve mobility, such as paving roads and constructing sidewalks, reduce the costs (in terms of time and money) of taking children to school (Lenhoff, Singer and Cook, 2020;Gottfried, 2017). Although a randomized control trial found no significant effects on school attendance after paving streets in Mexico (GonzalezNavarro and Quintana-Domeque, 2010), other factors besides paving may reduce mobility costs.…”
Section: A Theory Of Changementioning
confidence: 99%
“…There is, however, conflicting evidence on transportation costs and education in slums, suggesting the relationship might be negative(Lenhoff, Singer and Cook, 2020). This might be so because, in areas with high poverty, the means of transportation are heterogeneous.…”
mentioning
confidence: 99%
“…Research on school start times in an urban environment is needed. In addition to individual student characteristics, concentrations of poverty, neighborhood characteristics, and transportation issues unique to urban environments impact urban education and educational outcomes for students (Stein & Grigg, 2019; Silva-Laya et al, 2020; Pogodzinski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, families in a high poverty neighborhood may have fewer options available to help a student reach school if they oversleep and miss the bus. Transportation in urban environments can create a challenge to school attendance as students are more likely to rely on public transportation (Stein & Grigg, 2019; Pogodzinski et al, 2021). Thus, it is particularly important to understand the interplay between school start time and attendance within urban schools.…”
Section: Introductionmentioning
confidence: 99%